PENGARUH KEPUASAN KERJA DAN KOMITMEN AFEKTIF TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) : (Studi Pada Guru PAUD Kabupaten Sumedang) - Hasanah, Siti Fathimah Nurul; Suryadi, Edi; Askolani, Askolani (Jurnal Investasi, 2023)
This study was conducted to determine the effect of job satisfaction on organizational citizenship behavior with affective commitment as a mediating variable in PAUD teachers in Sumedang District. Organization need to develop its human resources in a way that can build the high level of Organizational Citizenship Behaviour (OCB). Job satisfaction and affective commitment can became an important factor which affecting OCB. The aim of this study is to identify the mediating role of affective commitment in the relationship between job satisfaction and OCB. The samples were derived from a survey using 20 items questionnaire distributed to the 64 teachers of early childhood education in Kabupaten Sumedang. The bootstrap confidence interval used to measure the mediation. The analytical techniques used in this study will use Structural Equation Modeling – Partial Least Square (SEM-PLS) analysis. The result revealed that there was a direct and indirect effect in the relation between job satisfaction and OCB. Since the interval did not contain zero in the equation, then the research found these relations was mediated by affective commitment. Affective commitment indeed contributes as mediator in the effect of job satisfaction on OCB.